Use of a micro title plate dilution assay to measure activity of antifungal compounds against mycosphaerella fijiensis, morelet. (2006)
Black Sigatoka, caused by the fungus Mycosphaerella fijiensis is the most important disease in banana plantations. The fungus is controlled mainly by fungicide applications with an annual cost of about 350 million dollars in Latin and Central America. Due to the appearance of resistant strains and to the economical and environmental impact caused by the extensive use of fungicides, accurate methods are necessary for monitoring the fungal sensitivity to these agents. In this paper we describe the standarization of a method basedmon microplate dilutions that measures IC50 of different antifungal compounds against single ascospore cultures of M. fijiensis. The method was used to measure the sensitivity of 30 strains collected from different regions in Colombia against Propiconazol, Benomyl and Azoxystrobin. Used at a larger scale, this method could be useful to monitor M. fijiensis sensitivity against fungicides and to search for new compounds with activity against the fungus.